(untitled) (Asian Education Studies, 2016)
The practices preschool teachers implement in their classrooms are vital in their students’ literacy development. Preschool teachers are always expected to implement research-based literacy practices to make sure children are ready to learn when they enter school. This multiple-case study intended to address four non-native in-service preschool English teachers’ practices in early literacy instruction. Data collection involved field notes and videotaping of classroom practices along with interviews and documents from ten full English lesson observations in each classroom. Data analysis began with identifying teachers’ practices. A cross case analysis was also conducted. The results showed that even when four teachers were in the same school district, using different curriculum, and supported by the different principal, each interpreted and enacted literacy policy differently. The overall conclusion generated from the results of the data analyses is that though teachers and preschool principals perceived that they were effectively applying early English literacy instruction, there was actually a divide between what teachers believed and what they implemented (their actual practice) in their classrooms. Besides, there was not enough interaction between teacher and children. However, the four preschool teachers mentioned in their interviews that they would like to be friends with their students.